Novos revestimentos para reatores à água pressurizada - um estudo neutrônico - Keila Macieira (2020)
The present work reports an analysis of neutronics behavior on cladding materials developed for Generation IV reactors with reliable application on commercial PWRs under operation. The advanced zirconium alloys, ZIRLO e OPT ZIRLO and the ceramic cladding silicon carbide (SiC) reinforced with Hi-Nicalon type S (SiC HNS) and FeCrAl alloy were chosen. A benchmark fuel element 17x17 with 4% fuel enrichment problem was used as reference case in order to validate the model analysis at steady-state and during burnup. In order to expand the neutronic studies of DEN-UFMG, the SERPENT Monte Carlo code was used for simulations. Of first order, the replacement has been made of the standard fuel cladding by different cladding materials comprised on this work. The infinite multiplication factor, fuel temperature coefficient of reactivity and moderator temperature coefficient of reactivity, thermal-to-total flux ratio and reaction rates neutronic parameters were evaluated during fuel depletion. The impacts of the reactivity control elements were also evaluated, through the use of burnable poison rods using the Zircaloy, ZIRLO, OPT ZIRLO, SiC HNS and iron-chrome-aluminum alloy claddings. At the end of this step, it was found that the FeCrAl cladding did not present satisfactory results when compared to other materials. For the next step, The ECB with FeCrAl alloy experienced changes in cladding thickness and fuel enrichment. All results compared with Zircaloy cladding shown that ones can replace the conventional cladding with at least two of the materials studied keeping the neutronic parameters advantages, the ceramic material SiC HNS and the iron-chrome-aluminum alloy with reduced thickness and increased fuel enrichment.